Principles And Characters Of Religious Moderation In Christian Religious Education - Doli Alberto Sagala (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2020)
This study aims to describe the inculcation of the value of religious moderation in Christian Religious Education. The research method used is descriptive qualitative. This study concludes that the cultivation of the value of religious moderation in Christian Religious Education is based on the principles of religious moderation: (1) fairness, (2) balance and character of religious moderation: (1) wisdom (2) sincerity (3) courage.